Some Comments on Rigorous Finite-Volume Euclidean Quantum Field Path Integrals in the Analytical Regularization Scheme - Luiz C. L. Botelho (Advances in Mathematical Physics)
Through the systematic use of the Minlos theorem on the support of cylindrical measures on 𝑅∞, we produce several mathematically rigorous finite-volume euclidean path integrals in interacting euclidean quantum fields with Gaussian free measures defined by generalized powers of finite-volume Laplacian operator.